Oxidation catalyst for exhaust gas purification and method for oxidizing exhaust gas using same

By forming a cerium-aluminum composite oxide catalyst layer on a three-dimensional structure and manufacturing CexAlyOz by ultrasonic treatment, the problem of insufficient NO oxidation performance in diesel engine exhaust gas under the prior art is solved, and CO, HC and NO in the exhaust gas is realized The efficient oxidation improves the waste gas purification effect.

CN119212787APending Publication Date: 2024-12-27UMICORE SHOKUBAI JAPAN CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202380040424.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-07
Filing Date
2023-06-26
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

It is difficult for the existing catalyst to efficiently oxidize NO in the exhaust gas of diesel engines to NO2 under low temperature conditions, affecting the exhaust gas purification effect.

Method used

CexAlyOz is produced by ultrasonic treatment using a cerium-aluminum composite oxide catalyst layer formed on a three-dimensional structure, including platinum, palladium and cerium-aluminum composite oxide or aluminum oxide, and CexAlyOz is produced by ultrasonic treatment (where x>y, x+y=1, 1.95≤z≤2.05) to improve the oxidation performance of the catalyst.

Benefits of technology

The oxidation performance of CO, HC and NO in the exhaust gas is significantly improved, especially under low temperature conditions, which can efficiently oxidize NO, enhancing the purification capacity of diesel engine exhaust gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005133926440000211
    Figure BDA0005133926440000211
  • Figure BDA0005133926440000241
    Figure BDA0005133926440000241
Patent Text Reader

Abstract

Provided is a catalyst capable of effectively oxidizing an exhaust gas (particularly NO). The present invention relates to an oxidation catalyst for exhaust gas purification in which a catalyst layer containing platinum, palladium, and a cerium-aluminum composite oxide or a cerium-aluminum composite oxide and an aluminum oxide is formed on a three-dimensional structure, the cerium-aluminum composite oxide containing CexAlyOz (wherein x > y, x + y = 1, 1.95 < = z < = 2.05).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an oxidation catalyst for purifying exhaust gas and a method for oxidizing exhaust gas using the same. Background Art

[0002] Many technologies have been proposed in the past for purifying exhaust gas generated by internal combustion engines. For example, for purifying exhaust gas from diesel engines, the particulate matter (PM) and nitrogen oxides (NO) contained in the exhaust gas are reduced. x ) for this purpose, various technologies have been proposed.

[0003] For example, Japanese Patent Publication No. 2002-211908 (US 2002 / 0090512 A1 in the same family) discloses a catalyst formed by loading a noble metal comprising at least platinum on a composite oxide, wherein cerium oxide and an oxide of at least one metal selected from Al, Ti and Si that do not solid-dissolve with the cerium oxide are dispersed at nanometer level in the composite oxide. The catalyst of Japanese Patent Publication No. 2002-211908 (US 2002 / 0090512 A1 in the same family) claims to have excellent durability. Summary of the invention

[0004] However, the catalyst disclosed in Japanese Unexamined Patent Application Publication No. 2002-211908 (the same family member is US 2002 / 0090512 A1) is a three-way catalyst, and thus, although it is effective for reducing NO x It is effective, but cannot exhibit sufficient oxidation performance (especially NO oxidation performance) for exhaust gas from diesel engines and the like.

[0005] Therefore, in view of the above circumstances, an object of the present invention is to provide a catalyst capable of efficiently oxidizing exhaust gas.

[0006] The present inventors have conducted intensive studies to solve the above problems and, as a result, have found that the above problems can be solved by using a specific cerium-aluminum composite oxide, thereby completing the invention.

[0007] That is, the above object is achieved by an exhaust gas purification oxidation catalyst, wherein a catalyst layer containing platinum, palladium, and a cerium-aluminum composite oxide or an aluminum oxide and a cerium-aluminum composite oxide is formed on a three-dimensional structure, wherein the cerium-aluminum composite oxide contains Ce x Al y O z (wherein, x>y, x+y=1, 1.95≤z≤2.05).

[0008] The present invention relates to an oxidation catalyst for purifying exhaust gas, wherein a catalyst layer containing platinum, palladium, and a cerium-aluminum composite oxide or a cerium-aluminum composite oxide and aluminum oxide is formed on a three-dimensional structure. The cerium-aluminum composite oxide contains Ce x Al y O z (wherein, x>y, x+y=1, 1.95≤z≤2.05) According to the catalyst of the present invention, exhaust gas can be effectively oxidized.

[0009] In order to purify the exhaust gas from the diesel engine, a urea SCR system is known. In this urea SCR system, it is important to provide the SCR catalyst with the amount of NO2 required for the Fast SCR reaction (4NH3+2NO+2NO2→4N2+6H2O). As a means of providing NO2, there is a known method of oxidizing NO by providing an oxidation catalyst on the exhaust path closer to the engine side than the SCR catalyst. However, under operating conditions where the exhaust gas temperature is low, it is difficult to efficiently carry out the oxidation reaction from NO to NO2, which is an important technical problem. We have conducted research with the purpose of solving the above-mentioned technical problems, and the results show that the catalyst having the above-mentioned characteristics can exert excellent exhaust gas oxidation performance (especially NO oxidation performance; the same below). Although the mechanism for producing the above-mentioned effect is not yet clear, it can be speculated as follows. It should be noted that the present invention is not limited to the following speculation. Ce x Al y O z (where x>y, x+y=1, 1.95≤z≤2.05), lattice defects tend to selectively appear at the interface between cerium oxide and aluminum oxide to compensate for the charge balance. It is believed that the lattice defects provide excess oxygen, which can promote NO oxidation.

[0010] In this specification, the "oxidation catalyst for exhaust gas purification" may also be referred to simply as "the catalyst according to the present invention" or "the catalyst". x Al y O z (wherein x>y, x+y=1, 1.95≤z≤2.05)" will also be referred to as "Ce x Al y O z " or "Ce x Al y O z In this specification, "including Ce x Al y O z(wherein, x>y, x+y=1, 1.95≤z≤2.05)" may also be referred to as "the cerium-aluminum composite oxide involved in the present invention" or "cerium-aluminum composite oxide". In the present specification, "the catalyst layer comprising platinum, palladium, and a cerium-aluminum composite oxide or an aluminum oxide and a cerium-aluminum composite oxide" may also be referred to as "the catalyst layer involved in the present invention" or "catalyst layer".

[0011] In this specification, "X and / or Y" means including at least one of X and Y, and covers "X alone", "Y alone" and "a combination of X and Y". In addition, in this specification, "X to Y" indicating a range includes X and Y, and means "more than X and less than Y".

[0012] The preferred embodiments of the present invention are described below. It should be noted that the present invention is not limited to the following embodiments, and various changes can be made within the scope of patent protection. In addition, the embodiments described in this specification can be combined in any way to form other embodiments.

[0013] Throughout this specification, when there is no special explanation, the expression in the singular form should be understood as also including the concept of its plural form. Therefore, when there is no special explanation, the article in the singular form (for example, "a", "an", "the", etc. in English) should be understood as also including the concept of its plural form. In addition, when there is no special explanation, the terms used in this specification should be understood as the meanings commonly used in the art. Therefore, if not defined otherwise, all the specialized terms and scientific and technological terms used in this specification have the same meaning as the conventional understanding of those skilled in the art in the field to which the present invention belongs. In the event of a conflict, this specification (including definitions) shall take precedence.

[0014] <Oxidation catalyst for exhaust gas purification>

[0015] The oxidation catalyst for exhaust gas purification involved in the present invention can efficiently oxidize CO, HC, NO (especially NO) in the exhaust gas. Therefore, the catalyst involved in the present invention can be combined with an SCR catalyst for the purpose of oxidizing the exhaust gas (especially NO) discharged from a diesel engine. That is, in a preferred embodiment of the present invention, the catalyst involved in the present invention is a catalyst for oxidizing the exhaust gas discharged from a diesel engine. In addition, the present invention also provides the use of the catalyst involved in the present invention for oxidizing the exhaust gas discharged from a diesel engine. In a more preferred embodiment of the present invention, the catalyst involved in the present invention is a catalyst for oxidizing NO in the exhaust gas discharged from a diesel engine. In addition, the present invention also provides the use of the catalyst involved in the present invention for oxidizing NO in the exhaust gas discharged from a diesel engine.

[0016] The technical features of the catalyst according to the present invention are described below in sequence.

[0017] [Cerium-aluminum composite oxide]

[0018] The catalyst layer involved in the present invention must contain Ce x Al y O z (wherein x>y, x+y=1, 1.95≤z≤2.05) a cerium-aluminum composite oxide.

[0019] Ce x Al y O z In the formula (A), x is greater than y (x>y), and x+y=1. x is greater than 0.5 and less than 1.00. If the substitution of Al in the CeO2 crystal structure is considered, x is preferably greater than 0.80 and less than 0.99, more preferably greater than 0.90 and less than 0.97, and particularly preferably 0.95. Similarly, if the substitution of Al in the CeO2 crystal structure is considered, z is greater than 1.95 and less than 2.05 (1.95≤z≤2.05). If further improvement based on the effect of the present invention is considered, z is preferably greater than 1.95 and less than 2.05, more preferably greater than 1.97 and less than 2.03, and particularly preferably 2.00.

[0020] That is, in a preferred embodiment of the present invention, Ce x Al y O z In a more preferred embodiment of the present invention, 0.80<x<0.99, x+y=1, 1.95<z<2.05. x Al y O z 0.90<x<0.97, x+y=1, 1.97<z<2.03. In a particularly preferred embodiment of the present invention, Ce x Al y O z For Ce 0.95 Al 0.05 O 2.00 .

[0021] Ce x Al y O z The presence of Ce can be confirmed by known methods, such as confirming the Ce content of the specified composition in X-ray diffraction (XRD). x Al y O z There is a peak at a specific measurement angle (2θ). For example, Ce x Al y O z For Ce 0.95 Al 0.05 O2.00 When the peak is detected, the presence of Ce can be confirmed by the method described in the examples. It should be noted that the "peak" can be detected by analyzing the XRD pattern using the analytical software used in the X-ray diffraction device for qualitative analysis or quantitative analysis. Therefore, when no peak is detected in the analytical software, it is judged that Ce does not exist. x Al y O z In addition, when there are two or more peaks in a specific range in the XRD spectrum, the peak with the highest intensity is selected.

[0022] Ce in cerium-aluminum composite oxide x Al y O z The amount of CeO2 can be determined by comparing the peak intensity of CeO2 observed in the XRD pattern with that of Ce x Al y O z The ratio of the peak intensities of CeO2 to Ce in the X-ray diffraction pattern (peak intensity ratio) is used as an indicator to confirm. x Al y O z The peak intensity ratio of CeO2 is less than 5.63, preferably less than 5.00, more preferably less than 4.21, further preferably less than 4.21, and particularly preferably less than 3.80. Within this range, the oxidation performance of exhaust gas can be further improved. x Al y O z The smaller the peak intensity ratio, the more preferred, but it is usually greater than 0, and can be greater than 1.17. In order to further improve the oxidation performance of exhaust gas, it is preferably greater than 1.24, more preferably greater than 1.66, and further preferably greater than 1.70. In the catalyst involved in the present invention, cerium oxide (cerium oxide) is preferably present only in cerium-aluminum composite oxide. That is, the catalyst layer involved in the present invention is preferably substantially free of cerium oxide except for cerium-aluminum composite oxide, and more preferably free of cerium oxide (the content of cerium oxide in the catalyst layer = 0 mass %). In this specification, "the catalyst layer is substantially free of cerium oxide" means that the content (loaded amount) of cerium oxide in the catalyst layer is less than 3 mass %, preferably less than 1 mass %.

[0023] In this specification, CeO2 is relative to Ce x Al y O z The peak intensity ratio of Ce can be obtained by the following method: x Al y O zThe peak intensity at the unique measurement angle (2θ) and the peak intensity at the unique measurement angle (2θ) of CeO2, the peak intensity of CeO2 divided by the peak intensity of Ce x Al y O z For example, Ce x Al y O z For Ce 0.95 Al 0.05 O 2.00 When CeO2 is relative to Ce 0.95 Al 0.05 O 2.00 The peak intensity ratio of CeO2 to CeO2 in the X-ray diffraction pattern can be obtained by the method described in the examples. x Al y O z The peak intensity ratio of CeO2 to Ce x Al y O z The peak intensity ratio of

[0024] The cerium-aluminum composite oxide of the present invention is preferably a composite oxide in which cerium element and / or cerium oxide (cerium oxide) are arranged in the form of islands in aluminum oxide (aluminum oxide), and more preferably a composite oxide in which at least a Ce-O- structure is arranged in the form of islands in aluminum oxide (aluminum oxide). In this case, Ce is formed at the boundary between aluminum oxide and cerium oxide. x Al y O z . By adopting this method, the effect of the present invention can be further improved. Therefore, the cerium-aluminum composite oxide involved in the present invention preferably contains more aluminum oxide than cerium oxide. Specifically, in the cerium-aluminum composite oxide involved in the present invention, the mass of cerium oxide is greater than 1 mass part and less than 50 mass parts, preferably greater than 2 mass parts and less than 20 mass parts, more preferably greater than 2 mass parts and less than 20 mass parts, further preferably greater than 3 mass parts and less than 10 mass parts, and particularly preferably greater than 3 mass parts and less than 10 mass parts, relative to 100 mass parts of cerium-aluminum composite oxide. With this composition, the oxidation performance of the exhaust gas can be further improved.

[0025] The loading amount of the cerium-aluminum composite oxide involved in the present invention is preferably 20 to 400 g, more preferably 50 to 300 g, and particularly preferably 80 to 200 g per 1L of the three-dimensional structure. When the content of the cerium-aluminum composite oxide in each 1L of the three-dimensional structure is 20 g or more, the effect of the cerium-aluminum composite oxide can be fully exerted. In addition, platinum and palladium can be fully dispersed in the cerium-aluminum composite oxide, and a catalyst with more excellent catalytic performance can be obtained. On the other hand, when the content of the cerium-aluminum composite oxide is 400 g or less, the contact state of platinum and palladium with the exhaust gas is good, and the exhaust gas oxidation performance can be more fully exerted.

[0026] In addition, the content of the cerium-aluminum composite oxide in the catalyst according to the present invention (in terms of solid content) is, for example, 20% by mass or more and less than 99.9% by mass, preferably 45% by mass or more and 99.5% by mass or less, and more preferably greater than 95% by mass and less than 99.5% by mass. At such a content, a good contact state between platinum and palladium and exhaust gas can be maintained, and the effect of the cerium-aluminum composite oxide can be fully exerted.

[0027] The present invention relates to Ce x Al y O z It can be produced by ultrasonically treating an aqueous solution containing a cerium source and an aluminum source. x Al y O z (wherein x>y, x+y=1, 1.95≤z≤2.05), which comprises the step of subjecting an aqueous solution containing a cerium source and an aluminum source to ultrasonic treatment.

[0028] Preferably, the Ce x Al y O z The method can be prepared as follows: adding a cerium source and an aluminum source to an acidic solution to prepare an aqueous solution 1 (aqueous solution 1 preparation step); applying ultrasonic waves to the aqueous solution 1 to prepare an aqueous solution 2 (aqueous solution 2 preparation step); adding the aqueous solution 2 to an alkaline solution to obtain a powder (powder preparation step); and calcining the powder (calcination step). The above method is described in detail below.

[0029] (Aqueous solution 1 preparation step)

[0030] In this step, a cerium source (cerium raw material) and an aluminum source (aluminum raw material) are added to an acidic solution to prepare an aqueous solution 1.

[0031] Here, as cerium source (cerium raw material), cerium acetate, cerium nitrate, cerium chloride, cerium sulfate, cerium sulfite, cerium complex salt etc. can be listed. The above-mentioned cerium raw material can be in the form of hydrate. Among them, preferably cerium chloride, cerium nitrate, more preferably cerium chloride. As aluminum source (aluminum raw material), aluminum acetate, aluminum nitrate, aluminum chloride, aluminum sulfate, aluminum sulfite, aluminum complex salt etc. can be listed. The above-mentioned aluminum raw material can be in the form of hydrate. Among them, preferably aluminum chloride, aluminum nitrate, more preferably aluminum chloride. The mixing ratio of cerium raw material and aluminum raw material is preferably the ratio of the composition constituting the cerium-aluminum composite oxide as described above.

[0032] The acidic solution for adding the cerium raw material and the aluminum raw material can be prepared by adding an acidic substance to a solvent. Here, as the acidic substance, for example, hydrogen chloride, sulfuric acid, nitric acid, etc. can be listed. Among them, hydrogen chloride and nitric acid are preferred, and hydrogen chloride is more preferred. In addition, as the solvent, water, lower alcohols (such as methanol, ethanol, propanol, isopropanol), etc. can be listed. The above solvents can be used alone or in a mixture of two or more. Among them, water is preferred. The concentration of the acidic substance in the acidic solution is, for example, 0.01 to 1 mol / L, preferably 0.05 to 0.5 mol / L.

[0033] The amounts of the cerium raw material and the aluminum raw material added to the acidic solution are such that the total concentration of the cerium raw material and the aluminum raw material becomes 1 to 40% by mass, more preferably 10 to 30% by mass.

[0034] (Aqueous solution 2 preparation step)

[0035] In this step, ultrasonic waves are applied to the aqueous solution 1 prepared in the above (aqueous solution 1 preparation step) to prepare aqueous solution 2. By applying ultrasonic waves to the aqueous solution 1, the Ce x Al y O z (Especially Ce 0.95 Al 0.05 O 2.00 ). It is believed that this is because the application of ultrasound can make Ce enter the Al2O3 framework. It should be noted that the above content is speculation and the present invention is not limited to the above content. Therefore, in this process, if the aqueous solution 1 is not subjected to ultrasound treatment, the Ce x Al y O z (Especially Ce 0.95 Al 0.05 O 2.00 ) cannot form sufficient quantity.

[0036] In this process, a device equipped with a conventional ultrasonic oscillation source can be used. For example, a commercially available ultrasonic cleaning machine can be used. The frequency of the ultrasonic treatment is, for example, 10 to 50 kHz, preferably 30 to 45 kHz. When the frequency of the ultrasonic treatment is within the above range, Ce vibrates well. As a result, Ce easily enters the Al2O3 framework, thereby more effectively forming Ce. x Al y O z (Especially Ce 0.95 Al 0.05 O 2.00 ), so it is preferred. It should be noted that the ultrasonic treatment can be continued at the same frequency, or the frequency can be switched during the treatment using a frequency oscillation switching mode. The number of frequency switching can be 1 or more. The ultrasonic treatment temperature (the temperature of the aqueous solution 1) is, for example, 20 to 60°C, preferably 30 to 50°C. When the ultrasonic treatment temperature is within the above range, the dispersibility of Al2O3 in the solvent increases. As a result, Ce becomes easier to enter the Al2O3 skeleton, and Ce can be formed more effectively. x Al y O z (Especially Ce 0.95 Al 0.05 O 2.00 The ultrasonic treatment time is, for example, 15 minutes to 2 hours, preferably 20 minutes to 1 hour. The energy application condition is, for example, 30 to 100 W / cm 2 , preferably 50 to 80 W / cm 2 When the above conditions are adopted, the Ce of the present invention can be efficiently formed. x Al y O z (Especially Ce 0.95 Al 0.05 O 2.00 ). It should be noted that the ultrasonic treatment may be performed while stirring the aqueous solution 1.

[0037] (Powder preparation process)

[0038] In this step, the aqueous solution 2 prepared in the above (aqueous solution 2 preparation step) is added to the alkaline solution to obtain a powder.

[0039] The alkaline solution can be prepared by adding an alkaline substance to a solvent. Here, as the alkaline substance, for example, hydroxides of alkali metals such as sodium hydroxide and potassium hydroxide; quaternary ammonium salts such as ammonia, tetramethylammonium hydroxide, and tetraethylammonium hydroxide; amines such as ethylenediamine and piperazine, etc. can be listed. Among them, ammonia is preferred. In addition, as solvents, water, lower alcohols (such as methanol, ethanol, propanol, isopropanol), etc. can be listed. The above solvents can be used alone or in combination of two or more. Among them, water is preferred. The concentration of the alkaline substance in the alkaline solution is, for example, 0.01 to 1 mol / L, preferably 0.05 to 0.5 mol / L.

[0040] The amount of the aqueous solution 2 added to the alkaline solution is such that the total concentration (solid content concentration) of the cerium raw material and the aluminum raw material becomes 1 to 30% by mass, more preferably 5 to 20% by mass.

[0041] When aqueous solution 2 is added to the alkaline solution, powder precipitation occurs. The powder can be separated by centrifugation, filtration, etc. The separated powder can be washed with water (e.g., deionized water, pure water, ultrapure water, distilled water) as needed, and the washing step can be performed only once or repeatedly.

[0042] In addition, the powder can be dried as needed. The drying conditions when the powder is dried are not particularly limited. The drying temperature is, for example, 50 to 170° C., preferably 70 to 150° C. The drying time is, for example, 10 to 100 hours, preferably 20 to 60 hours. In addition, the drying can be performed in the air or in an inert gas atmosphere.

[0043] (Baking process)

[0044] In this step, the powder obtained in the above (powder preparation step) is calcined.

[0045] Here, the calcination conditions are not particularly limited. The calcination temperature is, for example, 500 to 1000° C., preferably 600 to 900° C. The calcination time is, for example, 10 minutes to 3 hours, preferably 15 minutes to 1 hour. In addition, the calcination can be performed in air or in an inert gas atmosphere.

[0046] [Aluminum oxide (aluminum oxide)]

[0047] The catalyst layer according to the present invention may contain aluminum oxide (alumina) in addition to the cerium-aluminum composite oxide.

[0048] When the catalyst of the present invention contains alumina, the alumina is not particularly limited as long as it is a substance containing aluminum oxide, and examples thereof include activated alumina such as γ, δ, η, and θ-alumina, alumina containing lanthanum oxide, alumina containing silica, alumina containing silica-titania, alumina containing silica-titania-zirconium oxide, etc. These aluminas may be used alone or in combination of two or more.

[0049] The BET specific surface area of ​​alumina is not particularly limited, but is preferably 50 to 350 m 2 / g, more preferably 80 to 250 m 2 When the specific surface area is as high as 1000 nm, sufficient amounts of platinum and palladium (catalyst components) can be loaded on the aluminum oxide, which can increase the contact area between the catalyst component and the exhaust gas and adsorb the reactants. As a result, the overall reactivity of the catalyst can be further improved.

[0050] The amount of alumina loaded is not particularly limited, and is preferably 10 to 200 g, more preferably 50 to 100 g per 1 L of the three-dimensional structure. When the content of alumina per 1 L of the three-dimensional structure is 10 g or more, platinum and palladium can be fully dispersed in the aluminum oxide, and a catalyst with more excellent catalytic performance can be obtained. On the other hand, when the content of alumina is 200 g or less, the contact state between platinum and palladium and the exhaust gas is good, and the exhaust gas oxidation performance can be more fully exerted.

[0051] In addition, for cerium-aluminum composite oxides (especially Ce x Al y O z ) and alumina, relative to 100 parts by mass of aluminum oxide, the cerium-aluminum composite oxide (especially Ce x Al y O z ) is preferably more than 30 parts by mass and less than 150 parts by mass, and more preferably more than 35 parts by mass and less than 100 parts by mass. When it is such a mixing ratio, the exhaust gas oxidation performance can be more fully exerted. It should be noted that, in order to further improve the effect of the present invention, the catalyst layer involved in the present invention is preferably basically free of aluminum oxide except for the cerium-aluminum composite oxide, and more preferably free of aluminum oxide (the content of aluminum oxide in the catalyst layer = 0 mass %). In this specification, "the catalyst layer is basically free of aluminum oxide" means that the content (loading amount) of aluminum oxide in the catalyst layer is less than 3 mass %, preferably less than 1 mass %.

[0052] [Precious Metals]

[0053] The catalyst (catalyst layer) of the present invention contains platinum (Pt) and palladium (Pd) as precious metals. In order to further improve the effect of the present invention, the precious metals contained in the catalyst (catalyst layer) of the present invention are only platinum (Pt) and palladium (Pd).

[0054] The loading amount of platinum (Pt) is not particularly limited. For the sake of exhaust gas oxidation performance, it is preferably 0.01 to 20 g, more preferably 0.05 to 10 g, and most preferably greater than 0.5 g and less than 5 g in terms of precious metal per 1 liter of the three-dimensional structure.

[0055] The loading amount of palladium (Pd) is not particularly limited. In consideration of the exhaust gas (especially HC) oxidation capacity, it is preferably 0.01 to 20 g, more preferably 0.05 to 5 g, and most preferably 0.3 to 3 g per liter of the three-dimensional structure in terms of precious metal conversion.

[0056] In addition, for the mixing ratio of platinum to palladium, it is preferred that platinum is greater than palladium in consideration of exhaust gas oxidation performance. Specifically, the content ratio of platinum to palladium (platinum / palladium (mass ratio)) is greater than 1.0 and less than 7.0, preferably 2.0 to 5.0, and more preferably greater than 2.0 and less than 4.9. When the mixing ratio of platinum to palladium is within the above preferred range, the exhaust gas oxidation performance can be further improved.

[0057] The noble metal source (starting material of the noble metal) is not particularly limited, and materials commonly used in this field, such as water-soluble noble metal salts and noble metal complexes, can be used. These can be used in a modified manner depending on the method for preparing the catalyst.

[0058] The amount of the precious metal source is not particularly limited, and is preferably an amount that can achieve the above-mentioned loading amount and mixing ratio of each precious metal. It should be noted that when two or more precious metal sources are used in combination, the total amount of the precious metal source is preferably an amount that can achieve the above-mentioned loading amount and mixing ratio of the precious metal.

[0059] [Other added ingredients]

[0060] The catalyst layer of the present invention may further include other additives on the basis of platinum, palladium, cerium-aluminum composite oxide or alumina and cerium-aluminum composite oxide. Specifically, other additives include refractory inorganic oxides, alkali metals, alkaline earth metals, rare earth metals or oxides or sulfides thereof.

[0061] When the catalyst layer of the present invention comprises a refractory inorganic oxide (excluding cerium-aluminum composite oxide and aluminum oxide), examples of the refractory inorganic oxide include zeolite, titanium oxide, zirconium oxide, silicon dioxide, etc. (excluding cerium-aluminum composite oxide and aluminum oxide). These refractory inorganic oxides may be used alone or in combination of two or more.

[0062] When the catalyst layer of the present invention contains an alkali metal (excluding the case where it contains aluminum oxide), examples of the alkali metal include lithium, sodium, potassium, rubidium and cesium, preferably potassium. The alkali metal may be added alone or as a mixture of two or more.

[0063] When the catalyst layer of the present invention contains an alkaline earth metal (excluding the case where it contains aluminum oxide), the alkaline earth metal includes calcium, strontium and barium, preferably barium. The alkaline earth metal may be added alone or in the form of a mixture of two or more. Alternatively, at least one alkali metal and at least one alkaline earth metal may be added in combination.

[0064] When the catalyst layer of the present invention contains a rare earth metal (excluding the case of containing aluminum oxide), the rare earth metal is not particularly limited, and examples thereof include lanthanum (La), neodymium (Nd), yttrium (Y), scandium (Sc), and praseodymium (Pr). Among them, lanthanum, neodymium, yttrium, and praseodymium are preferred, and lanthanum and praseodymium are more preferred. These rare earth metals may be contained alone or in combination of two or more.

[0065] In a preferred embodiment of the present invention, the catalyst layer is composed of platinum, palladium and cerium-aluminum composite oxide. Alternatively, in a preferred embodiment of the present invention, the catalyst layer is composed of platinum, palladium, cerium-aluminum composite oxide and aluminum oxide. In a more preferred embodiment of the present invention, the catalyst layer is composed of platinum, palladium and cerium-aluminum composite oxide.

[0066] [Three-dimensional structure]

[0067] The catalyst involved in the present invention is a catalyst layer formed by loading platinum and palladium, and cerium-aluminum composite oxide or aluminum oxide and cerium-aluminum composite oxide on a three-dimensional structure (refractory three-dimensional structure). The catalyst layer involved in the present invention can load one layer on the three-dimensional structure, or can load two or more layers on the three-dimensional structure. In the latter case, each catalyst layer can be of the same composition or different compositions. In addition, on the basis of one or more catalyst layers involved in the present invention, other catalyst layers other than the catalyst components involved in the present invention can be provided. In this case, the catalyst layer involved in the present invention is preferably present on the side in contact with the exhaust gas (the outermost layer).

[0068] Here, the three-dimensional structure is not particularly limited, and the fire-resistant three-dimensional structure commonly used in this field can also be used. As a three-dimensional structure, for example, a heat-resistant carrier such as a honeycomb carrier having triangular, quadrilateral, or hexagonal through holes (gas flow ports, chamber shapes) can be used. The three-dimensional structure is preferably an integrally formed product (three-dimensional structure, integral structure weir), and preferably uses, for example, a monolithic carrier, a metal honeycomb carrier, a plugged honeycomb carrier having a filtering function such as diesel particulate filtration, a punched metal, etc. It should be noted that it is not necessarily a three-dimensional structure, and for example, a granular carrier can also be used. In addition, a spherical or corrugated carrier can be used.

[0069] The material of the three-dimensional structure can be a material generally referred to as a ceramic honeycomb carrier, and products made of cordierite, mullite, alumina, α-alumina, silicon carbide, silicon nitride, etc. are particularly preferred, and cordierite products (cordierite carriers) are particularly preferred. Other products that can be formed into an integral structure using oxidation-resistant heat-resistant metals including stainless steel, Fe-Cr-Al alloy, etc.

[0070] These monolithic carriers are manufactured by extrusion molding, a method of winding and fixing a sheet element, etc. The shape of the through hole (gas vent, chamber shape) can be optionally hexagonal (honeycomb), quadrilateral, triangular or corrugated (wave-shaped). The chamber density (number of chambers / unit cross-sectional area) is sufficient when it is 100 to 1200 chambers / square inch, preferably 200 to 900 chambers / square inch, and more preferably 200 to 600 chambers / square inch (1 inch = 25.4 mm).

[0071] <Method for producing an oxidation catalyst for exhaust gas purification>

[0072] The exhaust gas purification oxidation catalyst according to the present invention can be produced by appropriately referring to a known method, except that platinum, palladium, cerium-aluminum composite oxide or cerium-aluminum composite oxide and alumina, and other components added as needed are used as catalyst components. In one embodiment of the present invention, a method for producing the exhaust gas purification oxidation catalyst according to the present invention is provided, which comprises the steps of ultrasonically treating an aqueous solution containing a cerium source and an aluminum source to produce Ce x Al y O z (wherein, x>y, x+y=1, 1.95≤z≤2.05). In a preferred embodiment of the present invention, the method for producing an oxidation catalyst for exhaust gas purification of the present invention comprises (a) a slurry preparation step, (b) a slurry coating step, (c) a drying step, and (d) a calcination step. In a more preferred embodiment of the present invention, the method for producing an oxidation catalyst for exhaust gas purification of the present invention comprises the following steps: ultrasonically treating an aqueous solution containing a cerium source and an aluminum source to produce Cex Al y O z (where x>y, x+y=1, 1.95≤z≤2.05), will contain the Ce x Al y O z Or the Ce x Al y O z A slurry of aluminum oxide, a platinum source, and a palladium source is applied on the three-dimensional structure, dried to form a coating film, and the coating film is baked.

[0073] <Exhaust gas oxidation method>

[0074] The catalyst of the present invention can exert high oxidation performance on exhaust gas. Therefore, the present invention also provides a method for oxidizing exhaust gas, which has the step of treating exhaust gas using the oxidation catalyst for exhaust gas purification of the present invention. The catalyst of the present invention can exert high oxidation performance on exhaust gas discharged from a diesel engine, especially can exert excellent oxidation performance on nitrogen monoxide (NO) in the exhaust gas. Therefore, in a preferred embodiment of the present invention, a method for oxidizing diesel engine exhaust gas is also provided, which has the step of treating exhaust gas discharged from a diesel engine using the oxidation catalyst for exhaust gas purification of the present invention (especially oxidizing nitrogen monoxide (NO) in the exhaust gas). To use a diesel engine to determine the purification rate of exhaust gas, it is preferred to use an evaluation mode for exhaust gas restrictions, such as a Light Off test based on synthetic gas, a NEDC mode, a JC08 mode, a WLTC, a WHTC, a FTP75, a FTP1199, a NRTC, a NRSC mode, etc. For example, when evaluating with the NEDC mode, Article 83 of Annex 82 of the United Nations Economic Commission for Europe is followed.

[0075] Here, the NO concentration in the exhaust gas is not particularly limited, but is preferably 1 to 10,000 vol ppm, more preferably 10 to 5,000 vol ppm, and further preferably 20 to 1,000 vol ppm. In addition, the exhaust gas may contain HC or CO in addition to NO.

[0076] In the above embodiment, the HC concentration in the exhaust gas is not particularly limited, and is preferably 1 to 50,000 volume ppm C1, more preferably 10 to 10,000 volume ppm C1, and further preferably 50 to 1,000 volume ppm C1. In addition, the CO concentration in the exhaust gas is not particularly limited, and is preferably 10 to 50,000 volume ppm, more preferably 50 to 15,000 volume ppm, and further preferably 50 to 5,000 volume ppm.

[0077] In addition, the exhaust gas discharged from the diesel engine contains particulate components (particulate matter, PM). Therefore, in order to remove PM, it is preferable to use a three-dimensional structure with a filtering function. Alternatively, a filter for removing PM may be separately provided.

[0078] The space velocity (SV) of the exhaust gas may be a conventional velocity, preferably 1,000 to 500,000 hr -1 , more preferably 5,000 to 200,000 hr -1 The gas linear velocity may be a normal velocity, preferably 0.1 to 8.5 m / sec, more preferably 0.2 to 6.7 m / sec.

[0079] In addition, the catalyst of the present invention can maintain and exert excellent oxidation performance for low-temperature exhaust gas. Specifically, the catalyst of the present invention can exert excellent exhaust gas oxidation performance for low-temperature exhaust gas of 50 to 600°C (preferably below 300°C, and particularly preferably below 250°C). Similarly, the catalyst of the present invention can maintain and exert excellent oxidation performance even if it is exposed to high-temperature exhaust gas for a long time. Specifically, after the catalyst of the present invention is exposed to high-temperature exhaust gas of 650 to 900°C from an internal combustion engine for a long time, it can still exert excellent exhaust gas oxidation performance for low-temperature exhaust gas of 50 to 600°C. Therefore, for example, even when the oxidation catalyst for exhaust gas purification is arranged in the exhaust flow path of the exhaust port of an internal combustion engine (diesel engine) and high-temperature exhaust gas flows into the exhaust flow path for a long time, the exhaust gas can be oxidized efficiently.

[0080] Therefore, the catalyst of the present invention as described above or the catalyst produced by the method as described above can be exposed to exhaust gas at a temperature of 650 to 900°C, preferably 700 to 850°C. In addition, the time for which the catalyst of the present invention is exposed to the high-temperature exhaust gas (the time for the exhaust gas to flow in) is not particularly limited, and is, for example, 10 to 800 hours, preferably 16 to 500 hours, and more preferably 40 to 100 hours. Even after being exposed to such high-temperature exhaust gas, the catalyst of the present invention has high performance. In order to investigate the exhaust gas oxidation performance of the catalyst after being exposed to high-temperature exhaust gas in this way, it is effective to evaluate the exhaust gas oxidation performance (the catalyst's resistance to degradation) after subjecting the catalyst to a treatment of exposing it to exhaust gas at 650 to 900°C for 10 to 800 hours as a heat treatment.

[0081] It should be noted that the "temperature of the exhaust gas" in this specification refers to the temperature of the exhaust gas at the catalyst inlet. Here, the "catalyst inlet" refers to the portion of the exhaust pipe provided with an oxidation catalyst for exhaust gas purification, which extends from the catalyst end face on the exhaust gas inlet side to the internal combustion engine side up to 10 cm, and is the center portion of the exhaust pipe in the length direction (axial direction). In addition, the "catalyst bed" in this specification refers to the central portion between the catalyst end face on the exhaust gas inlet side of the above-mentioned exhaust pipe and the catalyst end face on the exhaust gas outflow side, and is the center portion of the exhaust pipe cross section (when the cross section of the exhaust pipe is not circular, the center of gravity of the exhaust pipe cross section is taken).

[0082] Although the embodiments of the present invention have been described in detail, this is only illustrative and exemplary and not restrictive. Obviously, the scope of the present invention should be interpreted according to the appended claims.

[0083] The present invention includes the following methods and solutions:

[0084] 1. An oxidation catalyst for exhaust gas purification, wherein a catalyst layer containing platinum, palladium, and a cerium-aluminum composite oxide or a cerium-aluminum composite oxide and an aluminum oxide is formed on a three-dimensional structure,

[0085] The cerium-aluminum composite oxide contains Ce x Al y O z (where x>y, x+y=1, 1.95≤z≤2.05);

[0086] 2. The exhaust gas purification oxidation catalyst according to 1. above, wherein the Ce x Al y O z For Ce 0.95 Al 0.05 O 2.00 ;

[0087] 3. The exhaust gas purification oxidation catalyst according to 1. or 2. above, wherein the X-ray diffraction pattern of CeO2 relative to Ce x Al y O z The peak intensity ratio is less than 5.00;

[0088] 4. The exhaust gas purification oxidation catalyst according to any one of 1. to 3. above, wherein the catalyst layer is composed of platinum, palladium and a cerium-aluminum composite oxide;

[0089] 5. The exhaust gas purification oxidation catalyst according to any one of 1. to 3. above, wherein the catalyst layer is composed of platinum, palladium, cerium-aluminum composite oxide and aluminum oxide;

[0090] 6. The exhaust gas purification oxidation catalyst according to any one of 1. to 5. above, wherein the content ratio of the platinum to the palladium is greater than 1.0 and less than 7.0 (mass ratio);

[0091] 7. The exhaust gas purification oxidation catalyst according to any one of 1. to 6. above, which is a catalyst for oxidizing exhaust gas discharged from a diesel engine;

[0092] 8. A Ce x Al y O z (wherein, x>y, x+y=1, 1.95≤z≤2.05), which comprises the step of ultrasonically treating an aqueous solution containing a cerium source and an aluminum source;

[0093] 9. The method for producing an exhaust gas purifying oxidation catalyst according to any one of 1. to 7., comprising the steps of: ultrasonically treating an aqueous solution containing a cerium source and an aluminum source to produce Ce. x Al y O z (wherein, x>y, x+y=1, 1.95≤z≤2.05);

[0094] 10. The method for producing an exhaust gas purification oxidation catalyst according to any one of 1. to 7. above, comprising the steps of: subjecting an aqueous solution containing a cerium source and an aluminum source to ultrasonic treatment to produce Ce x Al y O z (where x>y, x+y=1, 1.95≤z≤2.05), will contain the Ce x Al y O z Or the Ce x Al y O z and a slurry of aluminum oxide, platinum source and palladium source are coated on the three-dimensional structure, dried to form a coating film, and the coating film is calcined;

[0095] 11. A method for oxidizing exhaust gas (especially NO), comprising the step of treating the exhaust gas using the exhaust gas purification oxidation catalyst described in any one of 1. to 7. above. Example

[0096] The effects of the present invention are described with the following examples and comparative examples. The technical scope of the present invention is not limited to the following examples. It should be noted that, in the following examples, unless otherwise specified, the operation is carried out at room temperature (25° C.). In addition, unless otherwise specified, “%” and “parts” represent “mass %” and “mass parts”, respectively.

[0097] Manufacturing Example 1: Preparation of powder a

[0098] CeCl3·7H2O was weighed as Ce raw material 1, and AlCl3·6H2O was weighed as Al raw material 1 so that the mixing ratio of CeO2 and Al2O3 reached 5:95 (mass ratio). The weighed Ce raw material 1 and Al raw material 1 were added to 0.1 mol / L HCl aqueous solution so that the total concentration of Ce raw material 1 and Al raw material 1 reached 20 mass %, to prepare Ce / Al mixed solution 1.

[0099] 200 mL of the Ce / Al mixed solution 1 was placed in an ultrasonic treatment device (1510J-DTH manufactured by Emerson, Japan). While keeping the temperature of the Ce / Al mixed solution 1 at 40°C, an ultrasonic wave of 70 W / cm was applied at a frequency of 42 kHz. 2 The ultrasonic treatment solution was added dropwise to 200 mL of a 0.1 mol / L NH4OH aqueous solution and then filtered to obtain a light yellow powder. It should be noted that the amount of Ce / Al mixed solution 1 added to the NH4OH aqueous solution was such that the total concentration of Ce raw material 1 and Al raw material 1 reached 10% by mass.

[0100] The obtained powder was washed several times with distilled water, dried at 100°C for 48 hours, and then calcined at 650°C for 30 minutes to obtain powder a (CeO2 content = 5 mass %).

[0101] Manufacturing Example 2: Preparation of powder b

[0102] Powder b (CeO2 content = 10 mass %) was obtained in the same manner as in Manufacturing Example 1, except that the Ce raw material 1 and the Al raw material 1 in Manufacturing Example 1 were weighed in such a way that the mixing ratio of CeO2 and Al2O3 reached 10:90 (mass ratio).

[0103] Manufacturing Example 3: Preparation of powder c

[0104] Powder c (CeO2 content = 20 mass %) was obtained in the same manner as in Manufacturing Example 1, except that the Ce raw material 1 and the Al raw material 1 in Manufacturing Example 1 were weighed in such a way that the mixing ratio of CeO2 and Al2O3 reached 20:80 (mass ratio).

[0105] Manufacturing Example 4: Preparation of powder d

[0106] A powder d (CeO 2 content = 5 mass %) was obtained in the same manner as in Production Example 1 except that the ultrasonic treatment was not performed.

[0107] Example 1: Preparation of Catalyst A

[0108] Platinum nitrate was weighed as a Pt raw material, palladium nitrate was weighed as a Pd raw material, and the powder a prepared in Manufacturing Example 1 was weighed in a manner to achieve the ratio in Table 1. Nitric acid was added to pure water to make the pH 1.5, and then the powder a was added and stirred for 30 minutes. Then, after wet grinding for 14 hours at a rotation speed of 60 rpm using a wet grinder (ball mill), platinum nitrate and palladium nitrate were added dropwise in sequence while stirring the slurry to obtain slurry A1 (solid content concentration = 32% by mass). The average particle size (D50) of the catalyst component in the obtained slurry A1 was less than 5 μm.

[0109] The obtained slurry A1 was wash-coated on a cordierite carrier (diameter = 24 mm, length = 67 mm, 300 cells / square inch, 5 mils) so that its loading after calcination reached 111.44 g / L. Then, after drying at 150° C. for 15 minutes, it was calcined at 550° C. for 30 minutes to obtain Catalyst A.

[0110] Example 2: Preparation of Catalyst B

[0111] Catalyst B was obtained in the same manner as in Example 1 except that the powder b prepared in Preparation Example 2 was used instead of the powder a in Example 1.

[0112] Example 3: Preparation of Catalyst C

[0113] Catalyst C was obtained in the same manner as in Example 1 except that powder c prepared in Production Example 3 was used instead of powder a in Example 1.

[0114] Comparative Example 1: Preparation of Catalyst D

[0115] In order to achieve the ratios in Table 1, platinum nitrate was weighed as a Pt raw material, palladium nitrate was weighed as a Pd raw material, and aluminum oxide (BET specific surface area: 215 m 2 / g, average secondary particle size: 15 μm) and cerium oxide (BET specific surface area: 152 m 2 / g, average secondary particle size: 4μm). Nitric acid was added to pure water to make the pH 1.5, and then aluminum oxide and cerium oxide were added in sequence and stirred for 30 minutes. Next, after wet grinding at a rotation speed of 60 rpm for 14 hours using a wet grinder (ball mill), platinum nitrate and palladium nitrate were added dropwise in sequence while stirring the slurry to obtain slurry D1 (solid content concentration = 32% by mass). The average particle size (D50) of the catalyst component in the obtained slurry D1 is less than 5μm.

[0116] Catalyst D was obtained in the same manner as in Example 1 except that the slurry D1 prepared above was used instead of the slurry A1 in Example 1.

[0117] Examples 4-5: Preparation of Catalyst E and Catalyst F

[0118] In order to achieve the ratios in Table 1, platinum nitrate was weighed as a Pt raw material, palladium nitrate was weighed as a Pd raw material, and the powder b prepared in Preparation Example 2 and alumina (BET specific surface area: 215 m 2 / g, average secondary particle size: 15μm). Nitric acid was added to pure water to make the pH 1.5, and then powder b and alumina were added in sequence and stirred for 30 minutes. Next, after wet grinding for 14 hours at a rotation speed of 60 rpm using a wet grinder (ball mill), platinum nitrate and palladium nitrate were added dropwise in sequence while stirring the slurry to obtain slurry E1 (solid content concentration = 32 mass %) and slurry F1 (solid content concentration = 32 mass %), respectively. The average particle size (D50) of the catalyst component in the obtained slurries E1 and F1 is less than 5μm.

[0119] Catalysts E and F were obtained in the same manner as in Example 1 except that the slurries E1 and F1 prepared above were used instead of the slurry A1 in Example 1.

[0120] Comparative Example 2: Preparation of Catalyst G

[0121] In order to achieve the ratios in Table 1, platinum nitrate was weighed as a Pt raw material, palladium nitrate was weighed as a Pd raw material, and aluminum oxide (BET specific surface area: 215 m 2 / g, average secondary particle size: 15μm). Nitric acid was added to pure water to make the pH 1.5, and then alumina was added and stirred for 30 minutes. Next, wet pulverization was performed at a rotation speed of 60 rpm for 14 hours using a wet pulverizer (ball mill), and platinum nitrate and palladium nitrate were added dropwise in sequence while stirring the slurry to obtain slurry G1 (solid content concentration = 32% by mass). The average particle size (D50) of the catalyst component in the obtained slurry G1 was less than 5μm.

[0122] Catalyst G was obtained in the same manner as in Example 1 except that the slurry G1 prepared above was used instead of the slurry A1 in Example 1.

[0123] Comparative Example 3: Preparation of Catalyst H

[0124] In order to achieve the ratios in Table 1, platinum nitrate was weighed as a Pt raw material, palladium nitrate was weighed as a Pd raw material, and aluminum oxide (BET specific surface area: 215 m 2 / g, average secondary particle size: 15μm). Nitric acid was added to pure water to make the pH 1.5, and then alumina was added and stirred for 30 minutes. Next, wet pulverization was performed for 14 hours at a rotation speed of 60 rpm using a wet pulverizer (ball mill), and platinum nitrate and palladium nitrate were added dropwise in sequence while stirring the slurry to obtain slurry H1 (solid content concentration = 32% by mass). The average particle size (D50) of the catalyst component in the obtained slurry H1 was less than 5μm.

[0125] Catalyst H was obtained by using the slurry H1 prepared above instead of the slurry A1 in Example 1 and washing the slurry H1 on the cordierite carrier so that the loading amount after calcination reached 111.76 g / L.

[0126] Example 6: Preparation of Catalyst I

[0127] Platinum nitrate was weighed as a Pt raw material, palladium nitrate was weighed as a Pd raw material, and the powder a prepared in Manufacturing Example 1 was weighed in a manner to achieve the ratio in Table 1. Nitric acid was added to pure water to make the pH 1.5, and then the powder a was added and stirred for 30 minutes. Next, after wet grinding for 14 hours at a rotation speed of 60 rpm using a wet grinder (ball mill), platinum nitrate and palladium nitrate were added dropwise in sequence while stirring the slurry to obtain slurry I1 (solid content concentration = 32% by mass). The average particle size (D50) of the catalyst component in the obtained slurry I1 was 5 μm or less.

[0128] Catalyst I was obtained by using the slurry I1 prepared above instead of the slurry A1 in Example 1 and wash-coating the slurry I1 on the cordierite carrier so that the loading amount after calcination reached 111.76 g / L. Except for this, the operation was similar to Example 1.

[0129] Comparative Example 4: Preparation of Catalyst J

[0130] In order to achieve the ratios in Table 1, platinum nitrate was weighed as a Pt raw material, palladium nitrate was weighed as a Pd raw material, and aluminum oxide (BET specific surface area: 215 m 2 / g, average secondary particle size: 15μm). Nitric acid was added to pure water to make the pH 1.5, and then alumina was added and stirred for 30 minutes. Next, wet pulverization was performed for 14 hours at a rotation speed of 60 rpm using a wet pulverizer (ball mill), and platinum nitrate and palladium nitrate were added dropwise in sequence while stirring the slurry to obtain slurry J1 (solid content concentration = 32% by mass). The average particle size (D50) of the catalyst component in the obtained slurry J1 was less than 5μm.

[0131] Catalyst J was obtained in the same manner as in Example 1 except that the slurry J1 prepared above was used instead of the slurry A1 in Example 1.

[0132] Example 7: Preparation of Catalyst K

[0133] In order to achieve the ratio in Table 1, platinum nitrate was weighed as a Pt raw material, palladium nitrate was weighed as a Pd raw material, and the powder b prepared in Manufacturing Example 2 was weighed. Nitric acid was added to pure water to make the pH 1.5, and then the powder b was added and stirred for 30 minutes. Then, after wet grinding for 14 hours at a rotation speed of 60 rpm using a wet grinder (ball mill), platinum nitrate and palladium nitrate were added dropwise in sequence while stirring the slurry to obtain slurry K1 (solid content concentration = 32% by mass). The average particle size (D50) of the catalyst component in the obtained slurry K1 was less than 5 μm.

[0134] Catalyst K was obtained in the same manner as in Example 1 except that the slurry K1 prepared above was used instead of the slurry A1 in Example 1.

[0135] Comparative Example 5: Preparation of Catalyst L

[0136] Catalyst L was obtained in the same manner as in Example 1 except that powder d prepared in Production Example 4 was used instead of powder a in Example 1.

[0137] The compositions of the catalysts A to L obtained above are summarized in Table 1 below. In Table 1 below, "Pt" and "Pd" represent the loading amounts of platinum and palladium, respectively (in terms of precious metals) (g / L). In Table 1 below, "Al2O3" and "CeO2" represent the loading amounts of aluminum oxide and cerium oxide, respectively (in terms of oxides) (g / L). In addition, "Ce-Al complex" represents a cerium-aluminum composite oxide. "AlCe" represents the loading amount of cerium-aluminum composite oxide (in terms of oxides) (g / L), and "the amount of Al2O3 in the Ce-Al complex" and "the amount of CeO2 in the Ce-Al complex" represent the amount of Al2O3 in the cerium-aluminum composite oxide (in terms of oxides) (g / L) and the amount of CeO2 (in terms of oxides) (g / L), respectively. "The content of Ce-Al complex relative to the total loading amount" represents the proportion (mass %) of the cerium-aluminum composite oxide contained in the catalyst.

[0138] [Table 1]

[0139]

[0140] For the catalysts A to F, I, K and L obtained as described above, Ce was confirmed as follows 0.95 Al 0.05 O 2.00 The presence of CeO2 relative to Ce0.95 Al 0.05 O 2.00 The results are shown in Table 2 below.

[0141] -Ce 0.95 Al 0.05 O 2.00 Confirmation and CeO2 relative to Ce 0.95 Al 0.05 O 2.00 Determination of Peak Intensity Ratio—For each catalyst, X-ray diffraction (XRD) was performed under the following conditions to obtain an XRD spectrum.

[0142] (X-ray diffraction conditions)

[0143] X-ray diffraction measuring device: Spectris, X'Pert PRO

[0144] Radiation source: CuKα radiation

[0145] Measuring angle range (2θ): 25°~89°

[0146] Step distance: 0.013°

[0147] Scanning speed: 1.2° / min

[0148] Working voltage: 45kV

[0149] Working current: 40mA.

[0150] In the obtained XRD spectrum, the intensity of the peak observed in the range of 2θ value of 77.0° or more and less than 78.0° (peak intensity I A ) and the intensity of the peak observed in the range of 2θ values ​​of 76.0° or more and less than 77.0° (peak intensity I B Here, the peak containing Ce and Al and observed in the range of 2θ value of 77.0° or more and less than 78.0° is Ce. 0.95 Al 0.05 O 2.00 Therefore, when a peak is observed in the range of 2θ value of 77.0° or more and less than 78.0°, it is judged that Ce exists. 0.95 Al 0.05 O 2.00. Similarly, the peak observed in the range of 2θ values ​​of 76.0° or more and less than 77.0° is a peak unique to cerium oxide (CeO2). Therefore, when a peak is observed in the range of 2θ values ​​of 76.0° or more and less than 77.0°, it is judged that cerium oxide (CeO2) exists. In addition, if no peak is detected in the identification search of the XRD spectrum, it can be considered that it does not exist, and it is recorded as "-" in the following Table 2.

[0151] Next, the peak intensity I B Divide by the peak intensity I A Get the value (I B / I A ratio). B / I A Ratio” is the ratio of CeO2 to Ce 0.95 Al 0.05 O 2.00 When comparing cerium-aluminum composite oxides containing the same amount of CeO2 and Al2O3, I B / I A The smaller the ratio, the more Ce exists in the cerium-aluminum composite oxide. 0.95 Al 0.05 O 2.00 The larger the proportion.

[0152] In addition, the NO oxidation performance of the catalysts A to L obtained as described above was evaluated in the following manner. Specifically, the catalyst inlet temperature was increased from 100°C to 400°C at a rate of 20°C / min, and the catalyst was heated at a GHSV of 40,000 h. -1 The mixed gas (NO: 300 volume ppm; NO2: 0 volume ppm; O2: 10vol%; CO: 300 volume ppm; HC (only C3H6): 300 volume ppmC1; CO2: 6vol%; H2O: 6vol%; balance: N2) was passed through each catalyst (0.0303L) at a flow rate, and the NO2 concentration contained in the generated gas passing through the catalyst at 250°C and 300°C was measured, and the NO2 generation rate (%) of each catalyst was measured. The results are shown in Table 2 below. In addition, the purification rates of CO and HC were also calculated. The temperature at which the purification rate of each gas reaches 50% is recorded as T50 (°C), and the results are shown in Table 2 below. It should be noted that the lower the T50, the higher the flammability of each gas (the higher the catalytic performance).

[0153] [Table 2]

[0154]

[0155] It can be seen from Table 2 above that compared with catalysts D, G, H, J and L of Comparative Examples 1 to 5, catalysts A to C, E, F, I and K of the embodiments have significantly higher NO2 generation rates.

[0156] This application is based on Japanese patent application No. 2022-109527 filed on July 7, 2022, and the disclosed contents are incorporated herein by reference in their entirety.

Claims

1. An oxidation catalyst for exhaust gas purification, wherein a catalyst layer containing platinum, palladium, and a cerium-aluminum composite oxide or a cerium-aluminum composite oxide and an aluminum oxide is formed on a three-dimensional structure, The cerium-aluminum composite oxide contains Ce x Al y O z ,in, x>y, x+y=1, 1.95≤z≤2.

05.

2. The exhaust gas purification oxidation catalyst according to claim 1, wherein: What is said x the y A z For what? 0.95 the 0.05 A 2.00 。 3. The exhaust gas purification oxidation catalyst according to claim 1 or 2, wherein: X-ray diffraction diagram of CeO2 relative to Ce x Al y O z The peak intensity ratio is less than 5.

00.

4. The exhaust gas purification oxidation catalyst according to claim 1 or 2, wherein: The catalyst layer is composed of platinum, palladium and cerium-aluminum composite oxide.

5. The exhaust gas purification oxidation catalyst according to claim 1 or 2, wherein: The catalyst layer is composed of platinum, palladium, cerium-aluminum composite oxide and aluminum oxide.

6. The exhaust gas purification oxidation catalyst according to claim 1 or 2, wherein: The content ratio of the platinum to the palladium is greater than 1.0 and less than 7.0 in terms of mass ratio. 7 . The exhaust gas purification oxidation catalyst according to claim 1 , which is a catalyst for oxidizing exhaust gas exhausted from a diesel engine.

8. A Ce x Al y O z A method for producing a cerium source and an aluminum source comprising the step of ultrasonically treating an aqueous solution, wherein: x>y, x+y=1, 1.95≤z≤2.

05.

9. The method for producing an exhaust gas purifying oxidation catalyst according to claim 1 or 2, comprising the steps of: subjecting an aqueous solution containing a cerium source and an aluminum source to ultrasonic treatment to produce Ce. x Al y O z steps, where x>y, x+y=1, 1.95≤z≤2.

05.

10. A method for oxidizing exhaust gas, comprising the step of treating the exhaust gas using the exhaust gas purification oxidation catalyst according to claim 1 or 2.

Citation Information

Patent Citations

  • Compound oxide powder, manufacturing method thereof and catalyst

    JP2002211908A

  • Information processing system and information processing method

    JP2022109527A

  • Composite oxide powder, a method for producing the same and a catalyst using the same

    US20020090512A1

  • Preparation method of cerium-aluminum composite oxide with low cost and large specific surface area

    CN106732518A

  • Purification catalyst for internal combustion engine exhaust gases and exhaust gas purification method using said catalyst

    CN107530687A